Switching Among Biosimilars: A Review of Clinical Evidence - Allocati, Eleonora; Godman, Brian; Gobbi, Marco; Garattini, Silvio; Banzi, Rita (Frontiers in Pharmacology, 2022)
Biological medicines have improved patients’ outcomes, but their high costs may limit access. Biosimilars, alternatives which have demonstrated high similarity in terms of quality, safety and efficacy to an already licensed originator biological product, could increase competition and decrease prices. Given the expanding number of biosimilars, patients may switch from originator to biosimilar or among biosimilars. Randomized trials and observational studies conducted with multiple biosimilars over many disease areas confirmed the safety and efficacy of switching from originator to biosimilar. This study summarizes evidence on switching between biosimilars for which there are concerns to provide future guidance. Systematic search (Medline, Embase, Cochrane Library) for studies on anti-TNF agents, assessing clinical efficacy and safety of biosimilar-to-biosimilar switch in chronic inflammatory diseases. We retrieved 320 records and included 19 clinical studies. One study with historical control compared switching between biosimilars to maintenance of the same biosimilar. Ten were controlled cohort studies comparing switching between two biosimilars vs switching from originator to a biosimilar or vs multiple switches. Eight were single-arm cohort studies, where participants switched from one biosimilar to another and the outcomes were compared before and after the switch. Overall, these studies did not highlight significant concerns in switching between biosimilars. Therefore, switching studies seem difficult to perform and unnecessary with the body of evidence suggesting no real problems in practice coupled with stringent regulatory requirements. Monitoring the use of biosimilars in clinical practice, could support clinical decision making, rational use of biologic medicines, and help to further realize possible savings.